Association of mucoid degeneration of anterior cruciate ligament with knee meniscal and cartilage damage. Issue 9 (September 2015) - Kwee, R.M.; Ahlawat, S.; Kompel, A.J.; Morelli, J.N.; Fayad, L.M.; Zikria, B.A.; Demehri, S.
Summary: Objective: To assess the prevalence of anterior cruciate ligament (ACL) mucoid degeneration in patients referred for routine knee magnetic resonance (MR) imaging, and its association with age and structural joint damage. Method: Four independent radiologists assessed 413 consecutive knee MR examinations for the presence of a normal or ruptured ACL, or ACL mucoid degeneration. Knees with ACL mucoid degeneration were frequency matched by age, sex, and MR field strength with consecutive control knees with a normal ACL (1:2 ratio). Differences in meniscal and cartilage damage of the tibiofemoral compartments, as determined by the Whole-Organ MR Imaging Score (WORMS) system, were compared by Mann–Whitney U tests. Multivariable logistic regression analysis identified the association of ACL mucoid degeneration with severe MTFC cartilage damage (WORMS≥5). Results: Patients with ACL mucoid degeneration ( n  = 36; 36% males; median age 55.5 years, range: 26–81) were older than patients with a normal ( P  < 0.001) or ruptured ACL ( P  < 0.001), without sex predilection ( P  = 0.76), and were more frequently diagnosed at 3 T (12%) compared to 1.5 T (2%). Knees with ACL mucoid degeneration had statistically significantly more medial meniscal ( P  < 0.001) and central and posterior medial tibiofemoral compartment (MTFC) cartilage ( P  < 0.001) damage compared with control knees ( n  = 72), but there were no differences in patients ≤50 years ( P  = 0.09 and 0.32, respectively). In multivariable logistic regression, severe MTFC cartilage damage (WORMS≥5) was significantly associated with ACL mucoid degeneration (odds ratio 4.09, 95% confidence interval 1.29–12.94, P  = 0.016). Conclusion: There is a strong association between ACL mucoid degeneration and cartilage damage in the central and posterior MTFC, especially in patients >50 years.